Geomorphological correlation of the tectonically displaced Tejo River terraces (Gavião–Chamusca area,central Portugal) supported by luminescence dating - Martins, A., Cunha, P., Huot, S., Murray, A., Buylaert, J. (2012)
A suite of fluvial terraces (T1–T6,from top to bottom of the staircase) occur along a _70km stretch of the Tejo River in central Portugal, between the small towns of Gavião and Chamusca. Terrace correlation was based upon the following: (a)aerialphotograph analysis, geomorphological mapping and field topographic survey; (b) sedimentology of the terrace deposits, namely the maximum particle size, clast composition and lithofacies identification; and (c) K-feldspar infrared stimulated luminescence (IRSL) dating of the three lower terraces levels, as quartz optically stimulated (OSL) signal of the samples from these terraces was too close to saturation for all but two samples.The two upper terraces (T1andT2) lack suitable materials for luminescence dating (e.g.sands/silts),but also their probable ages are beyondthe upper range of the dating method. Fault saffecting terraces and older deposits have been reported. The luminescence dating results suggest that some assignments of local terrace remnants were in correct because of fault-related vertical displacements. The luminescence dating procedure also included a correction for anomalous fading in order to obtain more reliable estimates of the burial ages. The fading rate was identical for all samples, so for correlation of the terraces anomalous fading of the feldspar IRSL signal is considered not to be a significant problem.The T5 terrace has corrected ages of 42–99 ka,the T4 from 107 to 222 ka andtheT3 terrace has a minimal age of >300 ka. Fluvia lincision appears to have been principally controlled by regional uplift but also by localized movements along fault structures. Using the corrected ages of theT4 surface a time-averaged incision rate can be quantified as follows:(1) 0.29 m/ka for reach III, (2) 0.53 m/ka in the Chamusca area (east side on reach IV) and (3) 0.13 m/ka in the Mato Miranda area (west side on reach IV, the less uplifted block according to the geomorphic framework.